Integrasi Gamifikasi dalam Perancangan dan Pembangunan Website Pembelajaran Kosakata Bahasa Asing - Novia Rahman Nisa; Waworuntu, Alexander; Lumba, Ester (Research and Community Service UNIVERSITAS KALBIS, 2023)
Proficiency in foreign languages offers numerous benefits, with vocabulary mastery being a key aspect. In today's digital era, learning foreign language vocabulary is not limited to physical dictionaries but also extends to online platforms. This study developed a foreign language vocabulary learning website using gamification methods, focusing on Japanese and German languages. The gamification approach was implemented using the Octalysis framework, particularly emphasizing the core drives of Development & Accomplishment and Empowerment of Creativity & Feedback, incorporating game elements such as rewards, leaderboards, and timers. The website was evaluated using the Hedonic-Motivation System Adoption Model (HMSAM) to assess user interest (behavioral intention to use) and immersion levels. The results indicated a user interest level of 82.29% and an immersion level of 80.53%, demonstrating the website's effectiveness in foreign language vocabulary learning.